The Effect of Iron Status during Pregnancy on Hearing Functions in the Newborn. - Doorsian, Mona (Université d'Ottawa / University of Ottawa, 2017)
Background: Iron deficiency, anemia, and iron excess have been associated with altered hearing functions in children and adults. Animal studies suggest that iron deficiency during pregnancy negatively affect fetal auditory development. The relationship between maternal iron status and auditory functions in healthy term newborns has not been clearly elucidated among humans. The goal of this pilot study was to determine the relationship between markers of iron status during pregnancy and brainstem auditory function in healthy neonates. Methods: Pregnant women who gave birth at the Montfort Hospital were recruited to take part in this study (n=6). Within two weeks after birth, their newborn’s hearing function was assessed by wave amplitude, latency and inter-latency from the Auditory Brainstem Response (ABR) test. Markers of iron status, namely hemoglobin (Hb) and mean corpuscular volume (MCV), were collected retrospectively for the first and second trimester from the women’s medical chart. Results: Overall, no significant relationship was observed between maternal Hb and MCV concentrations and newborns auditory function. Although two significant Spearman correlations were observed (MCV and inter-latency I-V; r=0.87; p=0.005 and Hb and amplitude V; r=0.89; p=0.04), these findings may be due to chance because of multiple testing and the small sample size. Conclusion: Although iron is a key nutrient involved in the brain and auditory system development, we were not able to demonstrate a relationship between iron status during pregnancy and newborn hearing function. Prospective or intervention studies with a larger sample size and with more specific iron markers (ex. ferritin) are required to confirm these findings.
Keywords: Otoacoustic Emission (OAE); Auditory Brainstem Responses (ABR); Iron Deficiency Anemia (IDA); Hemoglobin (Hb); Mean Corpuscular Volume (MCV); Hematocrit (HCT)